Cryptocurrency: Adoption efforts and security challenges in different countries - Pandya Suhag; Mittapalli Murugan; Gulla Sri Vallabha Teja; Landau Ori (Holistica, 2019)
This research paper is a holistic review done on the rise of Blockchain and cryptocurrency, then elaborate about the great advantages of having a decentralized finance system. The existing scenarios from a sample of countries were reviewed in regards to their effort to adopt cryptocurrency to find some of the challenges like what are the security challenges this new monetary system faces, and limitations faced by different countries. A detailed analysis was done to answer some of the vital questions as such why cryptocurrency is banned in a few countries when other countries see cryptocurrency as a secured mode of payment transaction or what kind of security is provided by cryptocurrency compared to the traditional payments such as pay by cash, credit, or checks. Lastly, this paper also summarizes a high-level overview to propose recommended solutions to overcome the security concerns associated with the adoption of cryptocurrencies and how does the future of cryptocurrency look.